2003
DOI: 10.1177/004947550303300311
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistant Tuberculosis in Diabetes Mellitus: A Retrospective Study from South India

Abstract: This study was conducted in a tertiary care teaching hospital in south India to evaluate the association of drug resistant tuberculosis (TB) in diabetic subjects. There were: 361 subjects with positive mycobacterial culture and susceptibility tests results over a 3-year period; 267 (74%) acid-fast bacillus smear positive; and 94 (26%) smear negative cases. One hundred and seventy-seven (49%) had resistant isolates to any one first line antiTB drugs (resistant group) and 184 (51%) had isolates sensitive to all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…We found tuberculous adenitis as the most common type of extrapulmonary TB. However, other related studies have shown that tuberculosis of the spine (Potts disease) [5] and disseminated TB were the commonest [6]. The diagnosis of extrapulmonary TB is, however, usually difficult even in centres with sophisticated diagnostic facilities, as it usually requires biopsies and culture of various body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…We found tuberculous adenitis as the most common type of extrapulmonary TB. However, other related studies have shown that tuberculosis of the spine (Potts disease) [5] and disseminated TB were the commonest [6]. The diagnosis of extrapulmonary TB is, however, usually difficult even in centres with sophisticated diagnostic facilities, as it usually requires biopsies and culture of various body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…16 Two studies have shown a significant association between diabetes and multidrug-resistant TB (MDR-TB), suggesting that diabetic patients may be more than five times as likely to have infection with MDR-TB. 5,17 However, contrasting results from other studies suggest that there is no association, 18,19 others even show a lower prevalence of drug resistance to antituberculous therapy compared to patients without DM. 14 Though existing evidence is inconclusive, the data does raise concern about the effect of DM on the clinical picture, disease severity and outcome of TB infection.…”
Section: Dm May Be a Serious Co-morbidity Of Tbmentioning
confidence: 93%
“…Although multiple studies have reported a positive association, with ORs ranging from 1·2 to 8·5, others have found no association. [33][34][35][36][37] Furthermore, many studies did not control for body-mass index, which is often high in people with type 2 diabetes, and can be associated with subtherapeutic serum drug concentrations that might lead to acquired resistance. In addition, the classification of patients simply as having type 2 diabetes without further stratification by glycaemic control, treatment modality, or renal function might result in the mixing of patients with substantially differing susceptibilities to drug resistance.…”
Section: Comorbidities As Risk Factors For Mdrmentioning
confidence: 99%